2014
DOI: 10.18632/oncotarget.2155
|View full text |Cite
|
Sign up to set email alerts
|

A novel class I HDAC inhibitor, MPT0G030, induces cell apoptosis and differentiation in human colorectal cancer cells via HDAC1/PKCδ and E-cadherin

Abstract: Accumulation of genetic and epigenetic changes contributes to cancer development and progression. Compared with gene mutations or deletions, epigenetic changes are reversible, which alter the chromatin structure remodeling instead of changes in DNA sequence, and therefore become a promising strategy for chemotherapy. Histone deacetylases (HDACs) are a class of enzymes that responsible for the epigenetic regulation of gene expression. MPT0G030 is a potent and selective class I HDAC inhibitor which showed broad-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…We also found that SAHA decreased tumor size in lung cancer xenograft model (Supplementary Figure 5). Our results support that HDAC inhibitor show anti-cancer effect on various cancer cells including colorectal and lung [28, 29]. The susceptibility of lung cancer cells to SAHA was higher than that of normal lung cells.…”
Section: Discussionsupporting
confidence: 86%
“…We also found that SAHA decreased tumor size in lung cancer xenograft model (Supplementary Figure 5). Our results support that HDAC inhibitor show anti-cancer effect on various cancer cells including colorectal and lung [28, 29]. The susceptibility of lung cancer cells to SAHA was higher than that of normal lung cells.…”
Section: Discussionsupporting
confidence: 86%
“…HDACs can be divided into 4 classes: Class-I (HDAC1, 2, 3 and 8), Class-II (HDAC4, 5, 6, 7, 9 and 10), Class-III (SIRT1-7) and Class-IV (HDAC11) (16). Recent studies suggest that Class-I HDACs are upregulated in many malignancies, and that they inhibit the expression of specific tumor-suppressor genes through epigenetic modulation (17)(18)(19). Our previous studies demonstrated that high levels of HDAC3 expression and activity play a critical role in CCA, and that the inhibition of HDAC3 could induce apoptosis in CCA cells (20).…”
Section: Metformin Facilitates Bg45-induced Apoptosis Via An Anti-warmentioning
confidence: 99%
“…The body weights of treated mice were used as indicators of health [33]. AR-42 treatment did not affect mouse body weight, indicating that the mice did not experience evident toxicity in vivo (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%